Differentiation of Body Height of Boys and Girls from the Town of Żywiec During the Decade 1962 – 1972 - Jasicki, Bronisław (Anthropological Review, 1983)
The author has compared body height in age groups of boys and girls measured at ten years interval (1962 – 1972) in the town of Żywiec in Southern Poland. Totality of the material in each age group was divided into subgroups of “advanced” — children who went to school a year earlier than required by regulations, “normal” and “retarded” — those whose age was, due to various factors, older than ‘normal in a given grade. Secular changes during the decade considered were found. They were more marked in boys than in girls and the largest for “advanced” group. Differences between decades in body height of girls are more marked in younger age classes, they disappear with age.